2007
DOI: 10.2174/138161207780831338
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Asymmetric Dimethylarginine: Markers or Mediators in Cardiovascular Disorders?

Abstract: This is an electronic version of an article published in Current Pharmaceutical Design, 13 (16). pp. [1619][1620][1621][1622][1623][1624][1625][1626][1627][1628][1629] 2007. The definitive version is available online at:http://www.bentham.org/cpd/index.htmThe WestminsterResearch online digital archive at the University of Westminster aims to make the research output of the University available to a wider audience. Copyright and Moral Rights remain with the authors and/or copyright owners. Users are permitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 191 publications
0
7
0
Order By: Relevance
“…Several studies have suggested that increased systemic inflammation is associated with impaired arginine metabolism (3134). We therefore conducted two separate sets of experiments in both humans and mice to determine whether we could use this method to test the hypothesis that increased systemic inflammation alters flux through arginine metabolic pathways by decreasing bioavailability of arginine and its amino acid metabolites, and increasing the concentration of methylated arginines.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that increased systemic inflammation is associated with impaired arginine metabolism (3134). We therefore conducted two separate sets of experiments in both humans and mice to determine whether we could use this method to test the hypothesis that increased systemic inflammation alters flux through arginine metabolic pathways by decreasing bioavailability of arginine and its amino acid metabolites, and increasing the concentration of methylated arginines.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, endothelial dysfunction, by itself, worsens IR by altering transcapillary passage of insulin to target tissues, establishing a reverberating cycle that, if not interrupted, leads to the progression of vascular damage. ADMA has been identified as an independent predictor of morbidity and mortality in different setting of patients [6][7][8][9]27], probably because it reduces NO bioavailability [28], promotes inflammatory processes and the increase of acute phase inflammatory response proteins, as CRP [29], and interacts with the latter in affecting insulin sensitivity [30]. In confirmation of this, elevated ADMA levels have been documented in different clinical conditions as dyslipidemia [3], high BP [9], diabetes [4], hyperhomocysteinemia [5], and renal failure [2,6,7], all associated with endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting finding in the present study is that rosuvastatin treatment can significantly decrease serum ADMA levels in patients without AF recurrence, but not in patients with AF recurrence, which was probably due to the shorter treatment period of rosuvastatin in these subjects. There are now compelling data that ADMA is a biomarker for the progression of cardiovascular disease and there are some data emerging that ADMA, as a possible mediator, may be functionally important in many heart diseases 14 . ADMA leads to nitric oxide (NO) deficiency in many clinical settings by inhibiting all three NOS isoforms.…”
Section: Discussionmentioning
confidence: 99%